The Concept of (Gem-Set) in Topology, A Review (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The (Gem-Sets) were known since 2013 and because of their wide using in characterization of new topological concepts as: separation axioms, compactness, continuity and other important concepts, we introduced this article to give the most important previous studies about this subject as a historical study.